2022
DOI: 10.3389/fpubh.2022.1001828
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Big Five personality traits based on facial behavior analysis

Abstract: The personality assessment is in high demand in various fields and is becoming increasingly more important in practice. In recent years, with the rapid development of machine learning technology, the integration research of machine learning and psychology has become a new trend. In addition, the technology of automatic personality identification based on facial analysis has become the most advanced research direction in large-scale personality identification technology. This study proposes a method to automati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The multiple regression analysis identified several significant predictors of cyberbullying victimization among high school students, including the female gender, younger age, lower educational achievement, and higher daily use of the Internet. These findings are consistent with previous research that has identified demographic, academic, and internet usage factors as important predictors of cyberbullying experiences [ 98 , 99 , 100 , 101 ]. The identification of these risk factors has important implications for the development of targeted prevention and intervention strategies [ 38 , 102 ].…”
Section: Discussionsupporting
confidence: 92%
“…The multiple regression analysis identified several significant predictors of cyberbullying victimization among high school students, including the female gender, younger age, lower educational achievement, and higher daily use of the Internet. These findings are consistent with previous research that has identified demographic, academic, and internet usage factors as important predictors of cyberbullying experiences [ 98 , 99 , 100 , 101 ]. The identification of these risk factors has important implications for the development of targeted prevention and intervention strategies [ 38 , 102 ].…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, several studies have applied Deep Learning methods to predict the severity of psychological traits by analyzing human behavior. Notably, corporations like Amazon and Uber have leveraged such models in their hiring processes 20 – 23 , considering candidates' behavior on social media 12 , 15 , 24 – 29 , including meta-analyses 7 , 30 , digital traces 31 – 35 , acoustic speech analysis 36 , 37 , dynamics of facial emotional expressions 38 .…”
Section: Introductionmentioning
confidence: 99%